Smart attendance using RFID reader / Muhammad Afiq Syazwan Ahmad Badri - Ahmad Badri, Muhammad Afiq Syazwan (2021)
Smart Attendance using RFID Reader is a web-based application that integrated with the Internet of Thing (IoT) hardware to store the attendance data of the student during the class session by using their student card. The project was developed using specific software such as Arduino IDE, PHP, MySQL, and Bootstrap. Meanwhile, the hardware that implemented in this project was Node MCU and RC522 RFID for scanning the card and sending data to the online database. The software and hardware were integrated into the web-based attendance management system to record the attendance data. The purpose of Smart Attendance using RFID Reader was to help to reduce time-consuming when the users using the traditional method, such as recorded the attendance by using a piece of paper. Moreover, this system can save all the student’s detail and the record of attendance in classes. Then, the lecturer can get the exact data of the students’ attendance record with the computerized system. The development of Smart Attendance using RFID Reader used the System Development Life Cycle (SDLC) by implementing the waterfall method as the methodology. User acceptance testing based on the Technology Acceptance Model (TAM) was conducted with 30 participants of students from part one until part eight and staffs to see the acceptance of the system. The test contains two parts, the first part was demographic questions and the second part was divided into four categories and consists of 16questions. Results gained from the testing was positively accepted by most of the participants. Therefore, the proposed application proved can be beneficial to the students and staffs by reducing the time taken for the attendance and store the data into the database which can motivate other developers to help contribute for more future projects in the process of collecting the attendance.